Building literacy awareness through a community library - Tarigan, Bahagia; Sofyan, Rudy (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Every individual needs to survive and even succeed in their life. One of the ways to achieve such success is to be literate. Literacy makes people civilized and knows the purpose of their life. People need to build their awareness of the importance of literacy, one of which is through building reading literacy awareness. This paper aims at building literacy awareness through a community library built for the people in Regaji Village, Karo Regency, North Sumatra. This is a descriptive study taking the local people living in Regaji Village as the participants. Observations, interviews, and documentation were used to collect the data related to the past and current reading literacy awareness in this village. The data were analyzed qualitatively. The results of the data analysis show that the reading literacy awareness of the local people was still relatively low. However, after the presence of the community library in this village, the literacy awareness of the local people, especially children, has grown, indicated by their increased reading habits. This current situation should be maintained and developed so that all the children in this village keep aware of the importance of reading literacy that eventually helps them get success in their future life.